Auditoría Financiera para determinar la razonabilidad de los Estados Financieros de la Empresa Inox Hornos y Equipos de la ciudad de Riobamba, periodo 2019 - Moya Palacios, María Gabriela (2024)
ABSTRACT: During the examination period, the company faced issues with its financial information due to the use of an accounting system that didn't meet the company's requirements and needs. The objective was to conduct a Financial Audit to assess the reasonableness of the financial statements of "INOX Hornos y Equipos" for the 2019 period. Both deductive and inductive methods were employed, quantitative and qualitative in nature, with a non-experimental design of explanatory, exploratory, and descriptive level. The population and sample consisted of 33 workers from the financial department. As it was an audit, the following techniques were applied: interviews, surveys, observation, and documentary analysis; with instruments such as interview guides, questionnaires, and financial analysis. The financial audit of INOX Hornos y Equipos revealed significant findings in each of the three phases conducted. In the internal control evaluation and planning phase, weaknesses in function segregation were identified, emphasizing the need for a detailed review of internal controls to mitigate operational risks. During the execution phase of audit tests and procedures, discrepancies were found in the application of Generally Accepted Accounting Principles (GAAP), particularly regarding asset depreciation and inventory recording. In the results communication phase, the urgent need to implement corrective measures is highlighted, including improvements in accounting staff training, periodic internal control reviews, and adjustments to accounting policies. Keywords: Financial audit, financial statements, internal control.